Effect of P Concentration on Ti Silicide Formation in In‐Situ P Doped Epitaxial Si Films. Issue 10 (24th January 2019) - Park, Seran; Shin, Hyunsu; Ko, Eunjung; Ko, Dae‐Hong
Abstract : Herein, the effect of P concentration in highly P‐doped epitaxial Si films on the formation of Ti silicide therein are investigated. Ti films sputter‐deposited on P‐doped Si substrates are annealed at different temperatures, and the thus obtained samples are characterized by X‐ray diffraction (XRD) and transmission electron microscopy. The former technique revealed that the formation of C54 is suppressed by high P concentrations, while the resistivity of Ti silicide are shown to be independent of P concentration when the C54 phase is fully formed under the condition of sufficient thermal budget. Most importantly, this work confirms the occurrence of a silicidation delay in in situ P‐doped epitaxial Si films and demonstrates that this delay increases the temperature of the C49 to C54 phase transition of Ti silicide. Abstract : Titanium silicide is formed on the Si:P epilayer at different P concentrations and annealing temperatures, and the obtained samples are characterized by X‐ray diffraction and transmission electron microscopy. Through the result, we confirm that the C49 to C54 phase transition temperature of Ti silicide is dependent on P concentration rather than on the induced stress.